ANALISIS DAN PERANCANGAN SISTEM E-PROCUREMENT PADA SMK - PP NEGERI JAMBI - Marthiawati. H, Noneng; Kurniawansyah, Kevin; Nugraha, Hafiz (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
Currently, there are still quite a number of organizations who consider that remuneration is a cost component that needs to be minimized and a means that can increase unproductive behavior, which can lead to personal problems. To be able to prevent the emergence of problems and the increase in remuneration expenditure of an organization, it is necessary to have a remuneration system that is fair, appropriate, and cost effective. In the process of calculating the Additional Employee Income (TPP) carried out by SMK PP Negeri Jambi, Batanghari Regency, it is still manually with calculations based on absenteeism, performance, and employee discipline, after all data is obtained then input into Microsoft Excel. The purpose of this study is to simplify calculations, minimize time in the process of inputting and calculating, the process of delivering TPP information quickly and accurately. Where the modeling of this system uses a flow diagram of Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and this system design uses web / internet media and produces a web-based information system for additional employee income payments (TPP) at SMP Negeri Jambi Regency. Batanghari.